Типізація та моделювання гідравлічних модулів з одноштоковим гідравлічним циліндром - Іваніцькая, О. П. (НТУ "ХПІ", 2013)
All variety of hydraulic throttle actuators with hydraulic cylinders with a rod can be reduced to 16 hydraulic modules, depending on the direction of movement of the piston, the direction of the load, the presence or absence of restriction (or flow control), and its location in the inlet and drain pipes. Mathematical model of the 16 main types of hydraulic modules with vertical and horizontal hydraulic cylinder with a piston rod.
Keywords: гідропривід; модель гідродинамічна; рух поршня; навантаження; дросель